Mineralization of organic matter in microbialites and implications for microbialite reservoirs in Member IV of the Leikoupo Formation, Sichuan Basin, China - Zhong, Yuan; Li, Kunyu; Zhang, Zili; Qiao, Yanping; Su, Guiping; Zhao, Like; Zhang, Baoshou; Wang, Yunlong; Dou, Shuang; Yan, Wei; You, Jie (Frontiers in Earth Science, 2023)
Microbialites are important reservoirs for oil and gas. The mineralization of organic matter in microbialites during early diagenesis can produce acidic fluids that dissolve carbonate grains, and can also result in an alkaline pore water that precipitates cement. The mineralization of organic matter in microbialites and its effect on microbialite reservoirs have not yet been studied in detail. In this study, quantitative statistical analysis of the two-dimensional spatial occurrence of pores and microbial fabrics, in situ geochemical analysis of specific components (microbial, transitional zone, and fine spar fabrics), and qualitative evaluation of the implications for microbialite reservoirs were undertaken on microbialites from Member IV of the Leikoupo Formation, Sichuan Basin, China. The quantitative statistical analysis shows that pores are spatially associated with microbial fabrics, but porosity has a poor correlation with microbial fabric content. In situ geochemical data indicate that microbialites with different porosities experienced different processes of organic matter mineralization. The processes of organic matter mineralization such as oxidation and nitrate reduction can provide more dissolution micropores than the process related with sulfate reduction, whereas the process of organic matter mineralization related with Fe–Mn oxide reduction results in cementation. Micropores created by organic matter mineralization can act as fluid channels for later dissolution and are important in the development of microbialite reservoirs.